Evaluation of insulin resistance in individuals with severe obesity candidates for bariatric surgery - Almeida, Vivian Cristhyna Alves (2023)
Severe obesity is a disease that has reached worldwide proportions, and consequent increase in surgical treatment. This, besides reducing body fat, also helps to reduce associated comorbidities, such as insulin resistance (IR) and diabetes. The aim of this study was to evaluate IR in obese individuals in the preoperative period of bariatric surgery. A cross-sectional study was carried out with patients admitted for bariatric surgery at Hospital Universitário Oswaldo Cruz (HUOC-UPE) in Recife-PE. Insulin resistance was assessed by triglyceride-glucose index (TyG index) and Triglyceride/HDL-c ratio (TG/HDL). Body composition was obtained by dual X-ray emission densitometry (DEXA). Sociodemographic data, anthropometric and biochemical variables, physical activity level, and alcohol intake were also collected. Sixty patients participated, with a mean age of 38.88 ±9.67 years, the majority being female, with an education level of more than 10 years, classified as active and at low risk for alcohol dependence. Men presented significantly higher values for weight, neck circumference, waist circumference and lean body mass (Kg). The candidates had IR, by TyG index and TG/HDL ratio, with females showing higher TyG index (p=0.037). Therefore, evaluating insulin resistance by easily accessible parameters in the preoperative period allows the adoption of early intervention strategies and thus reduce the consequences from its non-treatment.